Sexual Gender-Based Violence in Greek Refugees Camp - Nadhifa, Khairunnisa; Fahadayna, Adhi Cahya (Jurnal Transformasi Global, 2020)
In 2015 the European Migrant Crisis pushed Europe to a new dimension of issues and problems. With the mass of people migrating into the region, Greece became one of the front-line countries to face the crisis by hosting the country's high refugee population. Due to their incapability to adjust and respond according to the needs and situation of the crisis, other issues rise within Greek settlements among refugees themselves where violence came into existence. Sexual and Gender-Based Violence (SGBV) appears in the refugee population that targeted women refugees living in the Greek camps. To know exactly why the causes of SGBV to happen in the first place against women refugees can be known through the effort of the Heise Model by Lori Michau to seek the root problems of the causes that drive the reason SGBV to exist within risky situations such as refugee camps. Through this Heise Model, the author seeks the causes of why SGBV happened in Greek refugee camps in 2015-2018 in covering four levels of societal, community, interpersonal, and individual.